FACE-TO-FACE SELLING INCREASES SALES PERFORMANCE OF REAL ESTATE AGENTS IN THE PHILIPPINES - Jose Mari M. Lee; Gina Suarez (International Journal of Accounting, Finance and Business, 2020)
Multifaceted selling of Philippines real estate condominiums, using direct marketing particularly face-to-face selling and internet marketing is progressively important to have a productive sales performance. This research was conducted for the purpose of identifying the real estate agents’ sales performance in high-end developer. Descriptive-correlation design was utilized to test the relationship between demographic variables and direct marketing. Structured survey questionnaire and one-on-one interview were used for data collection. The respondents were 27 real estate agents who are all using direct marketing mainly face-to-face selling and internet marketing in selling high-end condominiums in Metro Manila. From the findings, face-to-face selling has the greatest impact on the number of units sold than internet marketing. Through this result, the most effective direct marketing to attain the sales quota is through face-to-face selling. The researcher proposed a sales approach based on the findings of the study.